Evaluation of Efficacy of an Herbal Compound on Dry Mouth in Patients With Head and Neck Cancers: A Randomized Clinical Trial. (January 2016) - Ameri, Ahmad; Heydarirad, Ghazaleh; Rezaeizadeh, Hossein; Choopani, Rasool; Ghobadi, Ali; Gachkar, Latif
Dry mouth is a common complication of radiotherapy for head and neck cancers. This study compared the efficacy of an herbal compound containing Malva sylvestris and Alcea digitata (Boiss) with artificial saliva (Hypozalix) for improving the symptoms of dry mouth in head and neck cancer patients. The study examined a total of 62 subjects assigned to 2 groups. The herbal compound and Hypozalix were administered for 4 weeks. Efficacy was assessed using the visual analog scale and by grading the degree of dry mouth. Both groups showed a significant difference between visual analog scale before and following intervention. There was also a significant difference in visual analog scale between groups at 4 weeks after onset of intervention. The herbal group showed a significant difference between the grade of dry mouth before and after intervention, but no change was observed for grade of dry mouth in the Hypozalix group. This study supports the efficacy of the herbal compound for controlling symptoms of dry mouth in head and neck cancer patients.